2015
DOI: 10.1111/pere.12087
|View full text |Cite
|
Sign up to set email alerts
|

Same‐sex infidelity in heterosexual romantic relationships: Investigating emotional, relational, and communicative responses

Abstract: The present study explores emotional, relational, and communicative responses to different-sex and same-sex infidelity in heterosexual romantic relationships. Two-hundred and eighty-five men and women completed an online survey. Individuals were asked to read a scenario in which an imagined heterosexual partner engages in infidelity with a different-sex or same-sex person. Individuals were randomly assigned to one of these two conditions and then asked to complete several measures assessing their imagined emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Heterosexism can extend even to hypothetical instances of infidelity: heterosexual men and women report more negative emotional responses to imagined instances of mixed-sex compared to same-sex infidelity (Denes et al, 2015), suggesting that they view cheating with a same-sex partner as less of a threat to their romantic relationships and, by extension, may view same-sex sexual experiences, or even relationships, as less valid or genuine.…”
Section: Heterosexismmentioning
confidence: 99%
“…Heterosexism can extend even to hypothetical instances of infidelity: heterosexual men and women report more negative emotional responses to imagined instances of mixed-sex compared to same-sex infidelity (Denes et al, 2015), suggesting that they view cheating with a same-sex partner as less of a threat to their romantic relationships and, by extension, may view same-sex sexual experiences, or even relationships, as less valid or genuine.…”
Section: Heterosexismmentioning
confidence: 99%
“…Greater attributions of blame were linked to greater avoidance and benevolence, and in turn relationship termination. In another study, men and women reported more anger, hurt, and upset in response to different-sex vs. same-sex infidelities (Denes et al, 2015). Men also reported higher sexual arousal and lower breakup intentions in response to same-sex infidelity compared to different-sex infidelity.…”
Section: Resultsmentioning
confidence: 99%
“…Note that, a different study found that women indicated more upset for same- than for opposite-sex infidelity (Wiederman & LaMar, 1998). One possible explanation for these findings is that, in the case of same-sex infidelity, women would assume that their partner was homosexual (Denes et al, 2015), and thus, even if they were to forgive his infidelity, the continuation of the relationship would be unlikely. In this respect, women would prefer that their partner would cheat with a woman than with a man because, as opposed to the latter, in the former scenario the continuation of the relationship would be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Male participants did not indicate more distress than female participants in the case of the homosexual affair. Similarly, Denes, Lannutti, and Bevan (2015) employed an online sample of 285 participants in the USA and assessed four emotional responses, namely anger, hurt, upset, and fear, as well as willingness to terminate a relationship in the scenarios of same-sex and opposite-sex infidelity. They found that men and women experienced similar negative emotions across the two scenarios, but men were less likely to terminate the relationship in the case of same-sex infidelity.…”
Section: The Weak Selection Pressures Hypothesismentioning
confidence: 99%